Loss of cooperativity of secreted CD40L and increased dose-response to IL4 on CLL cell viability correlates with enhanced activation of NF-kB and STAT6 - Bhattacharya, Nupur; Reichenzeller, Michaela; Caudron-Herger, Maïwen; Haebe, Sarah; Brady, Nathan; Diener, Susanne; Nothing, Maria; Döhner, Hartmut; Stilgenbauer, Stephan; Rippe, Karsten; Mertens, Daniel (International journal of cancer, 2015)
Chronic lymphocytic leukemia (CLL) cells fail to enter apoptosis in vivo as opposed to their non-malignant B-lymphocyte counterparts. The ability of CLL cells to escape apoptosis is highly dependent on their microenvironment. Compared to non-malignant B cells, CLL cells are more responsive to complex stimuli that can be reproduced in vitro by the addition of cytokines. To understand the molecular mechanism of the environment-dependent anti-apoptotic signaling circuitry of CLL cells, we quantified the effect of the SDF-1, BAFF, APRIL, anti-IgM, interleukin-4 (IL4) and secreted CD40L (sCD40L) on the survival of in vitro cultured CLL cells and found IL4 and sCD40L to be most efficient in rescuing CLL cells from apoptosis. In quantitative dose-response experiments using cell survival as readout, the binding affinity of IL4 to its receptor was similar between malignant and non-malignant cells. However, the downstream signaling in terms of the amount of STAT6 and its degree of phosphorylation was highly stimulated in CLL cells. In contrast, the response to sCD40L showed a loss of cooperative binding in CLL cells but displayed a largely increased ligand binding affinity. Although a high-throughput microscopy analysis did not reveal a significant difference in the spatial CD40 receptor organization, the downstream signaling showed an enhanced activation of the NF-kB pathway in the malignant cells. Thus, we propose that the anti-apoptotic phenotype of CLL involves a sensitized response for IL4 dependent STAT6 phosphorylation, and an activation of NF-kB signaling due to an increased affinity of sCD40L to its receptor.
Online 15May 2014
Gesehen am 25.05.2020